Relationship among Serum Hydrocortisone and Impairment in Left Ventricle Diastolic Function with Subjects of Diabetes Mellitus - Afsheen Akbar, Zulfiqar Ali, Muhammad Ijaz, Yasir Ali Bhatti, Sadia Zia, Aamna Habib (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes mellitus (DM) is considered main dangerous feature for the expansion of cardiac metabolic and coronary disorders. Chronic Heart failure along conserved ejection fraction (EF %) were distinguished by the dysfunction of left ventricle diastolic phase (LVDD). Aim: Aim of subjects with elevated serum cortisol or hydrocortisone level establish with Cushing’s syndrome has to be related with the progression of the LVDD. Methodology: We select 42 patients Diagnosed with (DM) and 40 subjects with no DM. Which was underwent echocardiography assessment at multiple hospitals of Lahore within two years of duration. The functions of left ventricle were estimate and the percentage of before time diastolic rate from inflow to trans-mitral before time diastolic rate be considered while guide for diastolic purpose. Concentration of serum cortisol in Plasma, glucose levels, serum fasting cholesterol and triglyceride levels, along by means of anti glycemic medications plus additional scientific distinctiveness was estimated, as well as along its relationship among E/A was resolute by means of only one variable and multiple variable analysis. Results: Multiple variable linear regression study illustrate that log of E/A were confidently associated by age factor (P=0.018), blood pressure systolic phase (P=0.003) and hydrocortisone (P=0.037), in subjects of diabetes mellitus. Multiple variable analysis illustrate that hydrocortisone were completely associated by means of age (P=0.016) and glycated hemoglobin (P=0.011). Therefore no relationship found among E/A and serum hydrocortisone levels in control subjects. Conclusion: Raised levels of hydrocortisone concentration might elevate the possibility of rising in subjects of diabetes mellitus.